2012
DOI: 10.1016/j.biopsych.2012.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Angiogenesis and Progenitor Cell Proliferation Are Increased with Antidepressant Use in Major Depression

Abstract: Background Adult neurogenesis is coupled to angiogenesis in neurogenic niches in the dentate gyrus (DG) and increased by antidepressants in rodents. We hypothesized that, in major depressive disorder (MDD), antidepressants increase neural progenitor cells (NPCs) and capillaries in the human DG. Methods NPCs and capillaries, detected on hippocampal sections by immunohistochemistry for nestin, were quantified by stereology in matched MDDs (untreated, n=12), MDD treated with selective serotonin reuptake inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
236
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(264 citation statements)
references
References 97 publications
(139 reference statements)
21
236
6
Order By: Relevance
“…Nevertheless, this was the hallmark study which provided valuable data for human in vivo neurogenesis in depressive disease conditions. In contrast to this study, two recently published studies showed that antidepressant treatment in major depression patients increased the number of neural precursor cells and angiogenesis in the mid and anterior dentate gyrus [27]. The discrepancy between the two studies may be due to the use of different immunochemical markers and quantification methods, which should be verified in future studies.…”
Section: Neurogenesis and Depressive Disordercontrasting
confidence: 75%
“…Nevertheless, this was the hallmark study which provided valuable data for human in vivo neurogenesis in depressive disease conditions. In contrast to this study, two recently published studies showed that antidepressant treatment in major depression patients increased the number of neural precursor cells and angiogenesis in the mid and anterior dentate gyrus [27]. The discrepancy between the two studies may be due to the use of different immunochemical markers and quantification methods, which should be verified in future studies.…”
Section: Neurogenesis and Depressive Disordercontrasting
confidence: 75%
“…Determinants of hippocampal volume in MDD are not known. Like others (Reif et al, 2006), we did not detect fewer mitotic cells (Boldrini et al, 2009) or neural progenitor cells (NPCs) in the DG postmortem (Boldrini et al, 2009(Boldrini et al, , 2012 in untreated MDD subjects (o58-60 y old) compared to those with no major psychopathology. Notably, blocking (Santarelli et al, 2003) or blunting (Vollmayr et al, 2003) hippocampal proliferation in adulthood is not sufficient to induce depression-like behavior in mice.…”
Section: Introductionmentioning
confidence: 85%
“…The role of the anterior hippocampus (Sahay and Hen, 2007) in emotion regulation would be tied more closely to neurogenesis if effects on neurogenesis were confined to anterior DG. We found that antidepressant-treated MDDs have more mitotic cells and NPCs selectively in the anterior DG (Boldrini et al, 2009(Boldrini et al, , 2012. Therefore, we hypothesized that changes in GN number associated with MDD or antidepressant treatment will be localized to the anterior DG.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations